2013
DOI: 10.1155/2013/581973
|View full text |Cite
|
Sign up to set email alerts
|

The Pattern of Respiratory Disease Morbidity and Mortality in a Tertiary Hospital in Southern-Eastern Nigeria

Abstract: Background. Respiratory complaints are commonly encountered in medicine and respiratory diseases place a high burden on healthcare infrastructure. Healthcare planning should be based on adequate information: this study will help us to analyze the pattern of respiratory disease admissions in the medical wards in a developing country. Methods. The medical records of patients admitted into the medical wards over a 5-year period were retrieved and reviewed. Information obtained included demography, diagnosis, como… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
19
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 20 publications
8
19
2
Order By: Relevance
“…This 10‐year retrospective analysis of respiratory disease‐related mortality in hospitals of Tanzania found that respiratory diseases contributed to 12.9% of all in‐hospital deaths. This figure is slightly higher than that reported in Nigeria . A significant annual increase of mortality rates due to these diseases was observed.…”
Section: Discussioncontrasting
confidence: 65%
“…This 10‐year retrospective analysis of respiratory disease‐related mortality in hospitals of Tanzania found that respiratory diseases contributed to 12.9% of all in‐hospital deaths. This figure is slightly higher than that reported in Nigeria . A significant annual increase of mortality rates due to these diseases was observed.…”
Section: Discussioncontrasting
confidence: 65%
“…TB and HIV/AIDS were the leading causes of morbidity and mortality in patients admitted to our facility. In our study, pulmonary tuberculosis constituted about 44% of admitted respiratory cases which was comparable to reports from previous studies [10,11]. Pulmonary tuberculosis is a major health challenge in the developing countries and the burden is fuelled by the dual epidemics of HIV/AIDS and NCDs like diabetes mellitus [12].…”
Section: Discussionsupporting
confidence: 89%
“…In spite of the epidemics of the chronic noncommunicable diseases like cardiovascular and metabolic diseases in developing countries, as already established in the developed ones, communicable diseases are still a major threat. Erstwhile studies have been conducted in several parts of Nigeria on the profile of respiratory-related medical admissions [10,11], but none has been documented in Ekiti State University Teaching Hospital, Ado-Ekiti, Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the proportion of pathologies in the test set was uneven. Conversely, the strength of the study includes that although the sample was small and randomly selected, the case mix was fairly representative of common chest diseases in the study environment 25 and the number of readers was considerably high. Also, since X-ray interpretation is currently being undertaken by some radiographers in the private setting, an evaluation of their performance is timely and pertinent; therefore, the result of this study is worthy of consideration.…”
Section: Discussionmentioning
confidence: 99%